A study of financial risk propensity and the hedonic drivers of cryptocurrency investment - Anderson, Jason Nathaniel (My University, 2025)
A complete understanding of why individuals invest in cryptocurrencies has not yet been achieved, especially considering the asset’s volatility. Given that financial planning professionals are charged by the CFP Board to fully understand a client’s personal circumstances when offering financial guidance, a thorough understanding of the individual and predicting factors affecting cryptocurrency investment is warranted. Specifically, this dissertation aimed to uncover if financial risk propensity and hedonism influence the behavioral intention to, and actual adoption of, cryptocurrency for investing purposes. To learn more about these phenomena, this study used a secondary dataset, the National Financial Capability Study (NFCS), and gathered primary data using the Hedonic-Motivation System Adoption Model (HMSAM) and Domain-Specific Risk-Taking (DOSPERT) frameworks. Results from Structural Equation Modeling (SEM) and logistic regression show that the hypothesized relationship was supported for curiosity and joy (which had a positive relationship with behavioral intention [BI] and cryptocurrency investment) but rejected for the financial-gambling measure and perceived usefulness (PU).
Keywords: Cryptocurrency; Hedonism; Risk propensity; Gambling